Peran Aktif Generasi Muda Dalam Dunia Wirausaha - Fransisca Wuri Wulandari; Fadil Habiburahman (LPPM Politeknik Pajajaran ICB Bandung, 2025)
Discussions on entrepreneurship often position young people merely as objects of guidance rather than as agents of change. Young generations play a strategic role in fostering entrepreneurship in the era of digital transformation. This study aims to analyze the role of young people in entrepreneurship and identify the supporting factors and barriers influencing their interest and success. A quantitative descriptive method was employed, involving 100 respondents aged 18—30 years selected through purposive sampling. Data were collected using a closed-ended questionnaire with a 5-point Likert scale and analyzed using descriptive statistics. The findings indicate that young people play a significant role as innovators and agents of change, particularly in the utilization of digital technology (mean score 4.45). Entrepreneurial interest among respondents was high (80% categorized as high and very high interest). The main driving factor was technological advancement (35%), while the primary obstacle was limited capital (40%). This study concludes that although young people have substantial entrepreneurial potential, policy interventions such as access to capital and sustainable business mentoring are urgently needed to establish a conducive entrepreneurial ecosystem.